2020
DOI: 10.3389/fnins.2020.570750
|View full text |Cite
|
Sign up to set email alerts
|

Current Techniques for Investigating the Brain Extracellular Space

Abstract: The brain extracellular space (ECS) is a continuous reticular compartment that lies between the cells of the brain. It is vast in extent relative to its resident cells, yet, at the same time the nano-to micrometer dimensions of its channels and reservoirs are commonly finer than the smallest cellular structures. Our conventional view of this compartment as largely static and of secondary importance for brain function is rapidly changing, and its active dynamic roles in signaling and metabolite clearance have c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 102 publications
0
38
0
Order By: Relevance
“…The seal resistance (R s ) is given by R seal =ρ s •δ /d, where ρ s is the resistivity of the electrolyte solution (ρ s = 0.7 ΩCm), d is the average cleft width between the neuron's plasma membrane and the electrodes' surface, and δ is the overlapping surface coefficient that takes into account the percentage of the electrodes' sensitive area in contact with the microglia (Massobrio et al, 2016). Because of the unavoidable ~20% shrinking artifact of the extracellular spaces due to the chemical fixation of the tissue for TEM imaging (Korogod et al, 2015;Hrabetova et al, 2018;Soria et al, 2020) the actual width (d) of the clefts formed between the microglia and the implanted gMµEs-PPMPs surfaces cannot be extracted with precision from the ultrastructural images. In addition, the fraction of the surface area of the contact between a gMµE or planar electrode and the adhering microglia (δ) cannot be obtained from classical TEM images.…”
Section: Discussionmentioning
confidence: 99%
“…The seal resistance (R s ) is given by R seal =ρ s •δ /d, where ρ s is the resistivity of the electrolyte solution (ρ s = 0.7 ΩCm), d is the average cleft width between the neuron's plasma membrane and the electrodes' surface, and δ is the overlapping surface coefficient that takes into account the percentage of the electrodes' sensitive area in contact with the microglia (Massobrio et al, 2016). Because of the unavoidable ~20% shrinking artifact of the extracellular spaces due to the chemical fixation of the tissue for TEM imaging (Korogod et al, 2015;Hrabetova et al, 2018;Soria et al, 2020) the actual width (d) of the clefts formed between the microglia and the implanted gMµEs-PPMPs surfaces cannot be extracted with precision from the ultrastructural images. In addition, the fraction of the surface area of the contact between a gMµE or planar electrode and the adhering microglia (δ) cannot be obtained from classical TEM images.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma membranes, basement membranes, clefts in gap junctions, actin filaments, intermediate filaments, microtubules, ribosomes, extracellular spaces, glycogen granules, synaptic vesicles, dense-core vesicles, nuclear pores, and lysosomes, are only or best resolved with EM, at the highest resolution (reaching 1 nm) for a biological technique ( Tremblay et al, 2010b ; Savage et al, 2018 ; SynapseWeb, 2021 ). Although super-resolution microscopy, and more recently, expansion microscopy, were developed to resolve small structures, notably in correlation with EM ( Carrier et al, 2020 ; Hoffman et al, 2020 ; Parra-Damas and Saura, 2020 ; Soria et al, 2020 ), the capacity of EM to reveal the ultrastructure of cells and their constituents without selective staining (although staining can be used to provide better visualization of membranes, cytoskeletal elements, and ribosomes, for instance; Dykstra and Reuss, 2003 ; Svitkina, 2009 ) confers an important advantage ( Tremblay et al, 2010b ; Savage et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In retrospect, based on the preservation qualities of the cell membranes and subcellular organelles including the mitochondria, the smooth and rough endoplasmic reticulum, synaptic vesicles, post-synaptic densities and myelin, we concluded that the perfusion of the fixative was not impaired in the surroundings of the implant. It is important to note, however, that as in other ultrastructural studies of the CNS, the extracellular spaces between the various cell types is reduced by approximately 20% ( Korogod et al, 2015 ; Hrabetova et al, 2018 ; Soria et al, 2020 ). Since the volume of the implanted PPMPs is not altered by the fixatives, transcardial fixation led to the generation of mechanical tension around the implant.…”
Section: Resultsmentioning
confidence: 76%